2022
DOI: 10.1080/07853890.2022.2082518
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of faecal calprotectin in ulcerative colitis – single centre experience

Abstract: Objectives Faecal calprotectin is an important biomarker used in the evaluation of inflammatory bowel disease. The aim of this study was to establish the value of faecal calprotectin concentration as a predictor of remission in ulcerative colitis and its correlation with laboratory, endoscopic and clinical findings. Methods The single centre study included 126 adult patients with established diagnosis of ulcerative colitis consecutively visiting our Day clinic from Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…D'Amico et al (2020) indicated that there was a high statistically significant elevate in FC findings among active UC patients and patients in remission state [22] . Grgić et al (2022) reported significantly higher median FC in active UC patients (382,5 ug/g) versus inactive patients (44 ug/g) [23] . In this research, TFF3 was statistically significantly elevated in group I compared to group II and in group IA compared to group IB.…”
Section: Discussionmentioning
confidence: 98%
“…D'Amico et al (2020) indicated that there was a high statistically significant elevate in FC findings among active UC patients and patients in remission state [22] . Grgić et al (2022) reported significantly higher median FC in active UC patients (382,5 ug/g) versus inactive patients (44 ug/g) [23] . In this research, TFF3 was statistically significantly elevated in group I compared to group II and in group IA compared to group IB.…”
Section: Discussionmentioning
confidence: 98%
“…Because of the significantly lower levels in UC & Crohn's disease patient samples than in controls & IBS patient samples, reduced serum levels of intelectin-1 may be used to distinguish among studied cases with UC & healthy controls, as well as among IBS studied cases & healthy controls due to the nonsignificant variation in IBS patient & control samples (4). (7).…”
Section: Introductionmentioning
confidence: 99%